The non-stationary influence of the Atlantic and Pacific Niños on North Eastern South American rainfall - Torralba, Verónica; Rodríguez-Fonseca, Belén; Mohino, Elsa; Losada, Teresa (Frontiers in Earth Science, 2015)
Rainfall variability over the tropical Atlantic region is dominated by changes in the surface temperature of the surrounding oceans. In particular, the oceanic forcing over Northeast of South America is dominated by the Atlantic interhemispheric temperature gradient, which leads its predictability. Nevertheless, in recent decades, the SST influence on rainfall variability in some tropical Atlantic regions has been found to be non-stationary, with important changes of the Atlantic and Pacific influence on Sahelian rainfall which appear to be modulated at multidecadal timescales. In this work, we revisit the SST influence over Northeast of South America including the analysis of the stationarity of this relationship at interannual timescales. Principal Component Analysis has been applied to the interannual component of rainfall during the March-April-May season. Results show how the SST forcing on the first mode of rainfall variability, which is a dipole-like pattern generated by the changes in the seasonal migration of the Intertropical Convergence Zone, is different depending of the considered period. The response to the SST anomalies in the Pacific basin is opposite to the Atlantic one and affects different areas. The Atlantic Niño influences rainfall variability at the beginning of the XX century and after 1970, while the Pacific Niño plays a major role in the variability of the rainfall in the Northeast of South America from 1970 onwards. The combined effect of both basins after the 1970s amplifies the anomalous rainfall response.